The value of practice: A critique of interactional expertise. (April 2016) - Ribeiro, Rodrigo; Lima, Francisco PA
Collins and Evans have proposed a 'normative theory of expertise' as a way to solve the 'problem of demarcation' in public debates involving technical matters. Their argument is that all citizens have the right to participate in the 'political' phases of such debates, while only three types of experts should have a voice in the 'technical' phases. In this article, Collins and Evans' typology of expertise – in particular, the idea of 'interactional expertise' – is the focus of a detailed empirical, methodological and philosophical analysis. As a result, we reaffirm the difference between practitioners and non-practitioners, contesting the four central claims about interactional expertise – namely, that (1) the idea of interactional expertise has been proven empirically, (2) it is possible to develop interactional expertise through 'linguistic socialization alone', (3) the idea of interactional expertise supports the 'the minimal embodiment thesis' that the individual human body or, more broadly, 'embodiment' is not as relevant as linguistic socialization for acquiring a language and (4) interactional experts have the same linguistic fluency, understanding and judgemental abilities of practitioners within discursive settings. Instead, we argue, individuals' abilities and understandings vary according to the 'type of immersion' they have experienced within a given practice and whether they bring with them another 'perspective'. Acknowledging these differences helps with demarcation but does not solve the 'problem of demarcation'. Every experience is perspectival and cannot handle, alone, the intertwined and complex issues found in public debates involving technical matters. The challenge, then, concerns the ways to mediate interactions between actors with distinct perspectives, experiences and abilities.